KNOWLEDGE AND ATTITUDE REGARDING DENTIN-DISINFECTION CHEMICALS AMONG DENTAL STUDENTS, INTERNS, AND DENTISTS IN SAUDI ARABIA (CAHIERS MAGELLANES-NS, 2024)
Background: Bacteria in restorations can lead to secondary caries and pulpal pathology, prompting chemical antibacterial agents to disinfect the tooth structure before restorative procedures. Long-term success is significantly influenced by bacterial remnants in cavity walls. Microleakage causes dormant bacteria to multiply nutrients, leading to postoperative sensitivity, recurrent cavities, and pulpal irritation, ultimately causing restoration failure. The study aimed to assess Knowledge and attitude regarding Dentin-disinfection chemicals among Dental students, interns, and dentists in Saudi Arabia.Methods: This cross-sectional study was conducted using an online questionnaire among dental students, interns, and dentists in the KSA population. A structured questionnaire was employed as a study tool. This tool was developed after consulting relevant studies conducted in Saudi Arabia, the questionnaire consisted of 19 questions. Results: Regarding the knowledge and attitudes about dentin-disinfection chemicals among 1,012 dental students, interns, and dentists, we have found significant gaps in understanding. While a notable awareness of chlorhexidine (CHX) and sodium hypochlorite (NaOCl) was present, with 38.1% and 53.0% recognizing their specific concentrations, respectively, only 36.8% demonstrated a high overall awareness of these chemicals. Concerns were raised about NaOCl's adverse effects, and while 69% used these chemicals in practice, more than 49% showed little interest in attending related educational lectures. Despite some respondents recognizing a need for improved education, 73.7% exhibited low knowledge levels, which correlates with a significant proportion (37.9%) showing a low attitude towards the efficacy and safety of these agents.Conclusion: In conclusion, this study reveals considerable gaps in knowledge and attitudes concerning dentin-disinfection chemicals among Saudi dental students, interns, and practitioners. With a significant proportion demonstrating low knowledge and attitude. Focused educational interventions are critical to optimizing clinical practices and improving long-term patient results in restorative dentistry.